2002
DOI: 10.1152/ajpheart.00782.2001
|View full text |Cite
|
Sign up to set email alerts
|

Indexes of diastolic RV function: load dependence and changes after chronic RV pressure overload in lambs

Abstract: . Indexes of diastolic RV function: load dependence and changes after chronic RV pressure overload in lambs. Am J Physiol Heart Circ Physiol 282: H1350-H1358, 2002. First published December 13, 2001; 10.1152/ajpheart.00782.2001.-Diastolic function is a major determinant of ventricular performance, especially when loading conditions are altered. We evaluated biventricular diastolic function in lambs and studied possible load dependence of diastolic parameters [minimum first derivative of pressure vs. time (dP/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 41 publications
(53 reference statements)
11
63
2
Order By: Relevance
“…Basically, optimal coupling efficiency is achieved if contractility is matched to vascular load (Naeije & Manes, 2014). Pulmonary artery constriction selectively elevates RV afterload leading to a hyper-contractile response of the RV which was also shown at different time points after pressure overload induction in other species (Leeuwenburgh et al, 2002;Gaynor et al, 2005;Apitz et al, 2012). These and our data suggest that the observed contractility elevation together with RV dilatation and hypertrophy is insufficient to compensate for a dramatically increased afterload leading to ventricular-arterial decoupling and diminished RV ejection volumes.…”
Section: Discussionsupporting
confidence: 79%
“…Basically, optimal coupling efficiency is achieved if contractility is matched to vascular load (Naeije & Manes, 2014). Pulmonary artery constriction selectively elevates RV afterload leading to a hyper-contractile response of the RV which was also shown at different time points after pressure overload induction in other species (Leeuwenburgh et al, 2002;Gaynor et al, 2005;Apitz et al, 2012). These and our data suggest that the observed contractility elevation together with RV dilatation and hypertrophy is insufficient to compensate for a dramatically increased afterload leading to ventricular-arterial decoupling and diminished RV ejection volumes.…”
Section: Discussionsupporting
confidence: 79%
“…The periods of intermittent resting during the protocol may optimize the subendocardial coronary flow and, consequently, enlarge the quantity of substrates in the myocardial hypertrophic process, which limits the seriousness of a continuous systolic overload imposed upon the RV. This improvement in prerformance of the RV contrasts with the findings of Leeuwenburgh et al [26], which showed a drop in the cardiac debt in protocol of PT chronic banding in young sheep, despite the increase of RV contractility. The authors concluded that the chronic banding of the RV causes an increase in RV relaxation and decrease of the diastolic compliance, both indicative of diastolic dysfunction of the RV.…”
Section: Echocardiographic Parameterscontrasting
confidence: 99%
“…We used RV +/-dP/dt as reference values to evaluate RV systolic and diastolic functions. The RV peak +/-dP/dt are the most commonly used indices for assessing ventricular function [15,23,25,42]. However, these indices are influenced by ventricular preload and afterload.…”
Section: Discussionmentioning
confidence: 99%
“…However, these indices are influenced by ventricular preload and afterload. Therefore, other invasive indices of the ventricular function, such as maximal elastance (Emax), preload recruitable stroke work, chamber stiffness, and the time constant of relaxation (Tau), may reduce the impact from ventricular preload and afterload [15,25,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation